Building Criteria for Energy Labeling of Photovoltaic Modules and Small Systems. Issue 5 (30th September 2021) - Polverini, Davide; Amillo, Ana Gracia; Taylor, Nigel; Sample, Tony; Salis, Elena; Dunlop, Ewan D.
Abstract : As part of the Ecodesign framework, the European Union's energy‐labeling scheme has proved to be a powerful tool to communicate with consumers regarding the energy use of products. With sales of photovoltaic (PV) modules and small systems set to expand rapidly for the European Union to meet its commitments on CO2 reduction, ensuring that newly installed PV products in the European Union are environmentally friendly and do not create future burdens on the environment is of primary importance. Herein, an innovative methodology in support of a potential energy‐labeling scheme for both PV modules and PV systems (installations) is proposed. The estimated annual and lifetime yields for a PV module and system respectively are used as parameters for classification from A (best) to G (worst) in the proposed scheme. How to "translate" the methodology into a practical energy‐labeling scheme, i.e., for use in EU policy implementing measures, is also discussed. The conceptual challenges of proposing an energy label for energy‐generating products, i.e., PV modules and systems, are also discussed. Abstract : Herein, an innovative methodology is proposed in support of a potential energy‐labeling scheme (EU policy) for both photovoltaic modules and systems. The estimated annual and lifetime yields for a photovoltaic module and system respectively are used as parameters for classification from A (best) to G (worst) in the proposed scheme.